The Italian Public Pension System : Current Prospects and Reform Options - Canziani, Patrizia (IMF Working Papers; Working Paper ;, 1995)
Public pension expenditure in Italy has been growing rapidly in the last three decades and is now among the highest in industrialized countries. Despite recent reforms, benefits remain generous by international standards and, unless additional measures are taken, the financial situation of the system will deteriorate in the long term. The paper reviews the current system, its history, and its prospects, and examines through simulations the long-run effects of alternative pension reform options.